Cybersecurity and artificial intelligence: transformational strategies and disruptive innovation - Jahankhani, Hamid; Bowen, Gordon; Sharif, Mhd Saeed; Hussien, Osama (Advanced Sciences and Technologies for Security Applications, 2024)
This book discusses a range of topics that are essential to understanding cyber security, including legal implications and technical aspects, cyber detection, and minimising the threats so that governments and organisations can function without noticeable degradation of service. Unlike other technological threats, cyber security threats have the potential to destroy governments and undermine democratic processes - which makes an overarching cyber security strategy essential for all functioning governments. Thus, the book serves as a guide for developing strategies and ideas in the field and as a motivator for other governments and interested parties to develop and implement effective strategies. Arguably the most difficult aspect of these strategies is their implementation, which will require a cultural sea change in governments' approaches to handling cyber security and developing a regulatory framework that links organisations and governments in a secure working environment. The development of cyber security strategies calls for new skills at the technical and user levels alike. However, IT skills are sometimes in short supply, and without a government policy on cyber security training, the lack of these skills could hamper the full potential of cyber security. The book explores various aspects and challenges of cyber security strategy and highlights the benefits and drawbacks, offering in-depth insights into the field